Temporary heat stress suppresses PAMP-triggered immunity and resistance to bacteria in Arabidopsis thaliana - Janda, Martin; Lamparová, Lucie; Zubíková, Alžběta; Burketová, Lenka; Martinec, Jan; Krčková, Zuzana (Molecular plant pathology, 2019)
Recognition of pathogen-associated molecular patterns (PAMPs) is crucial for plant defence against pathogen attack. The best characterized PAMP is flg22, a 22 amino acid conserved peptide from flagellin protein. In Arabidopsis thaliana, flg22 is recognized by the flagellin sensing 2 (FLS2) receptor. In this study, we focused on biotic stress responses triggered by flg22 after exposure to temporary heat stress (HS). It is important to study the reactions of plants to multiple stress conditions because plants are often exposed simultaneously to a combination of both abiotic and biotic stresses. Transient early production of reactive oxygen species (ROS) is a well-characterized response to PAMP recognition. We demonstrate the strong reduction of flg22-induced ROS production in A. thaliana after HS treatment. In addition, a decrease in FLS2 transcription and a decrease of the FLS2 presence at the plasma membrane are shown after HS. In summary, our data show the strong inhibitory effect of HS on flg22-triggered events in A. thaliana. Subsequently, temporary HS strongly decreases the resistance of A. thaliana to Pseudomonas syringae. We propose that short exposure to high temperature is a crucial abiotic stress factor that suppresses PAMP-triggered immunity, which subsequently leads to the higher susceptibility of plants to pathogens.
Keywords: proteiny huseníčku; reakce na tepelný šok; Plant Immunity; PAMP-triggered immunity; Pseudomonas syringae; alarminy; heat stress; Arabidopsis thaliana; imunita rostlin; Arabidopsis; odolnost vůči nemocem; respirační vzplanutí; Transcription, Genetic; flg22; Arabidopsis Proteins; Respiratory Burst; regulace genové exprese u rostlin; nemoci rostlin; genetická transkripce; Disease Resistance; Gene Expression Regulation, Plant; Flagellin; flagelin; Heat-Shock Response; Alarmins; Plant Diseases; flagellin sensing 2 receptor; reactive oxygen species